Electronic processes in doped ZnO nanopowders - Grigorjeva, Larisa; Zolotarjovs, Aleksejs; Bite, Ivita; Grube, Jurgis; Millers, Donats (Institute of Physics Publishing, 2019)
ZnO nanocrystals, undoped and doped with Iridium or Indium were prepared by solar irradiation in Heliotron reactor in PROMES CNRS facilities, France. The comparative analysis of the excitonic spectra of ZnO single crystal and ZnO nanocrystals (NCs) doped with In and Ir was performed. It is shown that the excitonic processes in Ir doped nanocrystals coincide well with electronic processes in undoped NC and single crystal; however, the electronic processes in In-doped nanocrystals are significantly different from those in single crystal. The radioluminescence spectra of ZnO:In was analysed and additional luminescence band at ∼3.18 eV was detected due to In-doping. The luminescence decay time depends on In concentration in nanocrystals and is significantly less in ZnO:In compared with undoped nanocrystals. The fast scintillation of ZnO:In makes this material promising for application.
The financial support of research grants ERA.NET RUS_ST20170-051 and SFERA II project “Transnational Access activities” (EU 7th Framework Programme Grant Agreement N312643). This work was partly supported by the Russian Foundation for Basic Research, project no. 18-52-76002.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics